Audit energi sistem tata cahaya dan tata udara lantai 2 & 3 pada bangunan gedung toko buku di Pekanbaru - Awaludin Martin; Dhiky Rahman Agusta; Nehemia Simangunsong (Universitas Muhammadiyah Metro, 2022)
Energy audit is a technique used to analyze the amount of energy consumption in buildings and identify ways or methods to save it. Based on the Minister of Human Resources Regulation No. 13 of 2012 stated rules regarding energy management and energy saving standards. Shopping buildings are one of the sectors that use electrical energy to operate. A bookstore in Pekanbaru which consists of three floors also uses electrical energy for lighting and air conditioning systems. The use of electricity for lighting and air conditioning for a month is 37985.5 kWh and then ECO is carried out so that the use of electrical energy can be reduced to 30,138 kWh in each month. The use of electrical energy can be expressed in Energy Consumption Intensity (IKE), before the ECO IKE was carried out for the 2nd and 3rd floors of the bookstore building in Pekanbaru was 28.59 and after energy saving opportunities, the Energy Consumption Index became 23.09.